L.M. Salamon, S. Wojciech Sokilowski, and M.A. Haddock (2017), Explaining Civil Society Development. A Social Origins Approach, Baltimore: John Hopkins University Press - Anna Reggiardo (Coordinamento SIBA, 2018)
For Book Reviews abstract is not required